Analysis of loyalty and future intentions of the users of the golf courses in Andalusia, Spain - Marcos Pradas García; María José Maciá Andreu; Marta García-Tascón; Ana María Gallardo Guerrero (European Journal of Government and Economics (EJGE), 2020)
Spain is a European leader as a golf tourism destination, and Andalusia is the region that receives the most tourism in this sector, boosting not only the golf industry but also the percentage of income overall. Thus, user loyalty and knowing the future intentions of users is a matter of vital importance in these sports organizations. This study analyses 636 users of 17 golf courses in Andalusia -73.43% men and 26.42% women- and with an average age of 50.2 ± 15.6. The results show that more than 70% of users would encourage their families to play on the golf course and recommend it in more than 75% of them. In conclusion, this study emphasises the need for the use of the adapted tool, as it is a valid and reliable instrument that guides on the aspects demanded by the user as well as how to build loyalty.
Keywords: D7; D71; D9; D91; L83; Z2; Z21; 330; sports management; loyalty; golf courses